2021
DOI: 10.21203/rs.3.rs-559447/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Making Sense of a Pandemic: Mindsets Influence Emotions, Behaviors, Health, and Wellbeing During the COVID-19 Pandemic

Abstract: As the SARS-COV-2 virus spread across the world in the early months of 2020, people sought to make sense of the complex and rapidly evolving situation. This longitudinal study of N=5,365 Americans assessed three mindsets people formed about the COVID-19 pandemic and what it meant for their lives: ‘the pandemic is a catastrophe’, ‘the pandemic is manageable’ and ‘the pandemic can be an opportunity’. In line with our pre-registered hypotheses, these mindsets were associated with a unique and largely self-fulfill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Mindsets also differ from beliefs in that a mindset is not necessarily held to be true, but rather, is understood to be a selective viewpoint that may be useful in a given context. By using the term “mindset” we capture these nuances (e.g., while cancer may have negative impacts, it is something that can be accepted, dealt with, and to some degree controlled with medical intervention; Zion, 2021; Zion, Schapira, et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mindsets also differ from beliefs in that a mindset is not necessarily held to be true, but rather, is understood to be a selective viewpoint that may be useful in a given context. By using the term “mindset” we capture these nuances (e.g., while cancer may have negative impacts, it is something that can be accepted, dealt with, and to some degree controlled with medical intervention; Zion, 2021; Zion, Schapira, et al, 2019).…”
mentioning
confidence: 99%
“…In cancer survivors, illness mindsets have been related to physical, social, and emotional functioning, independent of disease characteristics (e.g., cancer stage) and psychological traits (e.g., trait optimism; Zion, 2021; Zion, Schapira, et al, 2019). Prior work suggests that mindsets may play an important role in the psychosocial outcomes of cancer survivors (Gutkin et al, 2020; Heathcote et al, 2020; Zion, Schapira, et al, 2019), who suffer disproportionate symptom burden compared with the general population (Lokich, 2019; Okonji & Ring, 2016).…”
mentioning
confidence: 99%
“…Prior to the pandemic, divergent thinking was associated with fewer depressive symptoms (Liknaitzky et al, 2018) and increasing divergent thinking in the context of the pandemic decreased anxiety symptoms (Zuo et al, 2021). Also, recent work has shown that mindsets about the pandemic had a selffulfilling pattern of quality of life 6 months later, such that stronger endorsement of a mindset that "the pandemic can be an opportunity" was protective (Zion et al, 2022). Efforts to increase divergent thinking, and tolerance of ambiguity, could also benefit from the cognitive behavioral and constructivist therapeutic approaches (Neimeyer, 2009;Hofmann et al, 2012) which have explicit goals of challenging undesirable perceptions of events to train increasingly functional ways of viewing the world.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer mindsets were measured using the cancer version of the Illness Mindset Inventory (IMI), a 9‐item measure of mindsets about illness, which was developed by experts in mindset research (including authors Zion, Dweck and Crum) 5 . The cancer version of the IMI consists of 3 subscales: cancer as a catastrophe, cancer as manageable, and cancer as an opportunity.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of mindsets about intelligence, stress, diet, and exercise on performance, health, and wellbeing outcomes of non‐clinical populations is well‐documented 2–4 . For patients with cancer, mindsets about the meaning of cancer and the role of the body may be similarly impactful 5,6 . By shaping a patient's cognitive, emotional, and physiological responses to both the illness and the subsequent treatment, these mindsets may influence multiple aspects of overall quality of life 2 .…”
Section: Introductionmentioning
confidence: 99%